Performing School Failure: Using Verbatim Theatre to Explore School Grading Policies (LEARNing Landscapes, 2020)
This article describes how dramatic writing and performance practices can be used to reshape qualitative interview data into a verbatim theatre performance with the intent of drawing attention to social movements in education. The performance described in the article reveals the consequences of a punitive educational policy agenda and addresses the emotional toll school grading and other neoliberal policies have had on teachers at a school in the southwestern United States. A primary objective is to examine and explore how verbatim dramatic writing and performance tactics can amplify current issues and social dilemmas and evoke an emotional response in the absence of dramatic action. The methods of writing a script from qualitative data are presented for other scholars and educators who intend to create performances from data.
Keywords: Neoliberalism in education; school grading; verbatim theatre